2015
DOI: 10.1371/journal.pone.0139435
|View full text |Cite
|
Sign up to set email alerts
|

The Overexpression of FEN1 and RAD54B May Act as Independent Prognostic Factors of Lung Adenocarcinoma

Abstract: Synthetic lethality arises when a combination of mutations in two or more genes leads to cell death. However, the prognostic role of concordant overexpression of synthetic lethality genes in protein level rather than a combination of mutations is not clear. In this study, we explore the prognostic role of combined overexpression of paired genes in lung adenocarcinoma. We used immunohistochemical staining to investigate 24 paired genes in 93 lung adenocarcinoma patients and Kaplan-Meier analysis and Cox proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Previous studies have reported that overexpression of FEN1 is positively correlated with poor prognosis of nonsmall-cell lung cancer [16] and breast cancer [17], as well as lung adenocarcinoma [22]. In addition, the gene has been proposed as a prognostic biomarker for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that overexpression of FEN1 is positively correlated with poor prognosis of nonsmall-cell lung cancer [16] and breast cancer [17], as well as lung adenocarcinoma [22]. In addition, the gene has been proposed as a prognostic biomarker for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…RAD54B is a known HR protein 25 and its elevated expression is associated with poor prognosis in colorectal 26 and lung 27 cancers. Consistently, our data in EAC shows that elevated RAD54B expression contributes to increased HR activity and genomic instability, and correlates with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…The clinicopathological features collected from the established database included risk factors, histological type, differentiation, and TNM stage. The histological diagnoses had been previously confirmed by two pathologists [18]. Patients with missing data or tissue loss during the IHC staining procedure were excluded from the study to reduce the bias from missing data.…”
Section: Patientsmentioning
confidence: 99%
“…The IHC staining was performed at the Department of Surgical Pathology, Changhua Christian Hospital using anti-human KLF17 antibody (abcam-84196; 1:100 dilution), as described previously [18,19]. Immunoreactivity was scored by the pathologists using a previously described scoring protocol [19,20].…”
Section: Immunohistochemical Staining Of Klf17mentioning
confidence: 99%
See 1 more Smart Citation